Chairman's report: African Elephant Specialist Group / Rapport du Presidente: Groupe des specialistes de l'elephant d'Afrique - Holly Dublin (Pachyderm)
Notes the African Range State Dialogue Meeting held in Dakar in November 1996, the cooperative investigations with TRAFFIC focused on the ongoing 'illegal' ivory trade and the ivory stocks, discusses the mandate of newly formed Task Force on Human-Conflict, and mentions the downlisting proposals for Namibian, Botswana and Zimbabwean populations being placed before the up coming COP10 meeting.